2006
DOI: 10.1111/j.1460-9592.2006.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of surfactant in spontaneous breathing with nCPAP: feasibility and outcome in extremely premature infants (postmenstrual age ≤27 weeks)

Abstract: Surfactant administration during nCPAP is feasible. First results indicate that early complications are rare. This warrants a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(216 citation statements)
references
References 10 publications
7
200
1
8
Order By: Relevance
“…Verder et al first published the results of their study on surfactant administration through a thin catheter in infants capable of spontaneous breathing in 1992 (21). However, this technique was first used as a treatment option in 2001 and the first serious study on the feasibility of this technique and its patient prognosis was published in 2007 (22,23 This technique appears to quickly improve infants 'physiological conditions and reduce their need for FiO 2 and mechanical ventilation and their duration of oxygen treatment (17).…”
Section: Discussionmentioning
confidence: 99%
“…Verder et al first published the results of their study on surfactant administration through a thin catheter in infants capable of spontaneous breathing in 1992 (21). However, this technique was first used as a treatment option in 2001 and the first serious study on the feasibility of this technique and its patient prognosis was published in 2007 (22,23 This technique appears to quickly improve infants 'physiological conditions and reduce their need for FiO 2 and mechanical ventilation and their duration of oxygen treatment (17).…”
Section: Discussionmentioning
confidence: 99%
“…New research on the differences between the allelic variants of the surfactant protein genes is leading to the understanding of individual susceptibility to the development of pulmonary diseases in the neonates. 30 Randomised controlled trials to evaluate the efficacy of combining prophylactic surfactant and early nasal continuous positive airway pressure in preterm infants 31,32 also need to be done in our country to evaluate and establish the most effective and safest interventions for preterm neonates at risk of developing RDS and associated morbidities. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the feasibility and an improvement of outcomes of the study group compared with a historical control group. 8 The need for mechanical ventilation because of RDS was reduced from 77% in the historical control group to 48% in the study group. Mortality decreased from 35 to 12% and the rate of severe IVH in survivors from 32 to 5%.…”
mentioning
confidence: 95%